2017
DOI: 10.1155/2017/9824698
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Immunogenic Response to Allogeneic Mesenchymal Stem Cells and the Role of Preactivated Mesenchymal Stem Cells Cotransplanted with Allogeneic Islets

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells capable of differentiating into cells from the mesenchymal lineage. The hypoimmunogenic characteristic of MSCs has encouraged studies using allogeneic MSCs for the treatment of autoimmune diseases and inflammatory conditions. Promising preclinical results and the safety of allogeneic MSC transplantation have created the possibility of “off-the-shelf” clinical application of allogeneic cells. This study has aimed to evaluate the survival of untreated and IFN-γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 55 publications
4
36
0
Order By: Relevance
“…Immune reactions and short engraftment time have also been described by Tano et al [ 64 ] in a model of allogeneic MSC transplantation on the epicardial surface of rat hearts. A similar paradigm has been confirmed recently by Oliveira et al [ 65 ] in a preclinical model of MSC transplantation in the murine kidney. They observed lymphocytic infiltration and allogeneic MSC rejection no later than 28 days after transplantation.…”
Section: Discussionsupporting
confidence: 70%
“…Immune reactions and short engraftment time have also been described by Tano et al [ 64 ] in a model of allogeneic MSC transplantation on the epicardial surface of rat hearts. A similar paradigm has been confirmed recently by Oliveira et al [ 65 ] in a preclinical model of MSC transplantation in the murine kidney. They observed lymphocytic infiltration and allogeneic MSC rejection no later than 28 days after transplantation.…”
Section: Discussionsupporting
confidence: 70%
“…The different immunogenicity of donor‐derived MSCs/HI‐MSCs in the transplant model and syngeneic MSCs/HI‐MSCs in the CLP model should also be considered when interpreting the in vivo effects in both models. It has been demonstrated that allogeneic MSCs are immunogenic and can sensitize the recipient, a factor that is not present in the case of syngeneic MSCs. However, the overall immunogenic potential of allogeneic MSCs seems to be less compared with other allogeneic cell types, and MSCs' immunogenicity seems not be determining for the differential effects of MSCs and HI‐MSCs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data from preclinical studies and clinical trials strongly suggest that even though allogeneic MSCs display immunoprivilege under in vitro conditions, late after transplantation in the host microenvironment, MSCs become immunogenic and provoke an immune response resulting in rejection. 12,24,56 We found that hypoxic or ischemic environment in the host tissue leads to the upregulation of CIITA and cell surface immune antigen MHC-II in rat and human MSCs. In the current study, we also found that preventing hypoxia-induced MHC-II upregulation in MSCs by knocking down Sug1 preserved the immunoprivilege of MSCs in vivo in the ischemic heart, mitigated host immune response, and improved survival of transplanted cells in a rat model of myocardial infarction.…”
Section: Discussionmentioning
confidence: 88%